2021
DOI: 10.1111/jfpe.13821
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive identification of barley seeds variety using near‐infrared hyperspectral imaging coupled with convolutional neural network

Abstract: Nondestructive inspection of varietal purity of seeds plays an important role in crop improvement, agricultural production, and plant breeding. In the present study, a rapid and nondestructive technique, that is, near-infrared hyperspectral imaging (NIR-HSI) was applied to discriminate the barley seeds variety. A large dataset of 35,280 seeds was collected from different locations and years incorporating 35 Indian barley varieties (29 hulled and 6 naked barley varieties). The hyperspectral reflectance images o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…This researcher suggested that the main limitation of this work is that it requires manual adjustment of sunflower seeds before they are captured on camera. In Table 5, the results obtained in this study were compared with the studies on the classification of barley cultivars in recent years (Hailu & Meshesha 2016;Dolata & Reiner 2018;Kozlowski et al 2019;Shi et al 2021;Singh et al 2021). Dolata & Reiner (2018) reported an accuracy rate of 97.24%.…”
Section: Web-based Model Deploymentmentioning
confidence: 84%
See 2 more Smart Citations
“…This researcher suggested that the main limitation of this work is that it requires manual adjustment of sunflower seeds before they are captured on camera. In Table 5, the results obtained in this study were compared with the studies on the classification of barley cultivars in recent years (Hailu & Meshesha 2016;Dolata & Reiner 2018;Kozlowski et al 2019;Shi et al 2021;Singh et al 2021). Dolata & Reiner (2018) reported an accuracy rate of 97.24%.…”
Section: Web-based Model Deploymentmentioning
confidence: 84%
“…According to our research with 14 barley cultivars, the fine-tuned DenseNet-169 model was performed better than other models and the state-of-the-art literature. On the other hand, Singh et al (2021) achieved the best accuracy rate of 98.38% with CNN because of near-infrared hyperspectral imaging.…”
Section: Web-based Model Deploymentmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, this classification was mostly performed using machine vision algorithms (Liu et al, 2021;Xu et al, 2021). At present, many algorithms have been used for the classification of bruises in fruits, for example, linear discriminant analysis, decision trees, Principal component analysis, Bayesian classifiers, support vector machines, and artificial neural networks (Baranowski, Mazurek, & Pastuszka-Woźniak, 2013;Boulent, Foucher, Theau, & St-Charles, 2019;ElMasry et al, 2008;Singh, Garg, & Iyengar, 2021;Wang et al, 2011;Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These methods work very well even with highly collinear data, but it is commonly known that they do not perform well when there are very many classes to separate. An example of this is presented by Singh et al 3 where 35 types of barley are analyzed using near‐infrared hyperspectral imaging with the aim to discriminate varieties. The study showed that PLS‐DA decreases abruptly in performance as the number of varieties grows.…”
Section: Introductionmentioning
confidence: 99%